The axiological diversity of the European far right in the first half of the 20th century - Pisarski, Marcin (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The subject of the article is the issue of axiological diversity of political movements of the far right, understood on the basis of metapolitics, i.e. religious, philosophical or civilizational values. The far right considered on this ground allows us to define the so-called ideological core, i.e. the characteristics of this political trend.
Keywords: far right; political axiology; political science of religion; conservative revolution; nationalism